La soledad en Clen anos de soledad de Gabriel Garcia Marquez - Potgieter, Petronella (School of Languages and Literatures, 2019)
This thesis analyses the theme of solitude in Gabriel García Márquez’s Cien años d e soledad given that it is the novel’s main theme, as suggested by the title and illustrated by the author’s focus on it and its related subthemes. The analysis of the novel and the associated literature aims to explain the author’s viewpoint on solitude and illustrate how this emotion affects the author’s homeland (Colombia) and its people as reflected in his work and through characters. The historical context of the novel and pre-Columbian myths form part of the analysis due to their role in understanding solitude as described by García Márquez. The Introduction to the thesis presents the author’s perspective on solitude– he equates it to anti-solidarity–underlining that solitude is recurrent in the work of García Márquez who stated that he only wrote one book in many books, namely the 'book of solitude’. This highlights the significance of this theme and related subthemes. The Introduction then places the novel in the literary period in which it was written (namely the Latin American boom) and examines the particular style (magic realism) that formed part of this era. Thereafter, a short biographic overview of the author is provided, with emphasis on his early childhood and the history of his time, these aspects having influenced his work profoundly. Finally, attention is drawn to pre-Columbian history as this constitutes the point of departure of the current study, in which various themes are explored to determine their link to solitude. Chapter 1 explores the theme of solitude in Latin American literature in particular and then goes on to show which non-Latin American authors also influenced García Márquez Chapter 2 deals with the historical context of the novel and its characters. It refers to the importance of history in García Márquez’s work. The pre-Columbian myths of Bachué and Hunzahúa are delved into as they too focus on solitude and incest, fundamental themes in Cien años de soledad. In addition, the characters affected by solitude are considered from an archetypal perspective. Chapter 3 is an analysis of the sub-themes of solitude and forms the biggest part of the thesis. Special attention is paid to solitude in relation to incest, lack of love, the quest for knowledge, power, nostalgia and death to show their interrelatedness and mutual influence. Cursory reference is made to other relevant aspects such as illegitimacy, insanity, elderliness, repetition, oblivion, narcissism, solipsism, fate and time. The Conclusion shows that in the specific geographic and historical context, the sub-themes analysed are in fact all themes of solitude in this novel and that solitude is the cause of the apocalyptic demise of Macondo and its people. It reveals that solidarity would be the factor that could save Colombia and Latin America.